2017
DOI: 10.1016/j.celrep.2017.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of TXNIP by AKT Mediates Acute Influx of Glucose in Response to Insulin

Abstract: SUMMARY Growth factors, such as insulin, can induce both acute and long-term glucose uptake into cells. Apart from the rapid, insulin-induced fusion of glucose transporter(GLUT)4 storage vesicles with the cell surface that occurs in muscle and adipose tissues, the mechanism behind acute induction has been unclear in other systems. Thioredoxin interacting protein (TXNIP) has been shown to be a negative regulator of cellular glucose uptake. TXNIP is transcriptionally induced by glucose and reduces glucose influx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
190
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(207 citation statements)
references
References 32 publications
6
190
0
Order By: Relevance
“…Other groups have previously shown that TXNIP deficiency induces AKT activation via oxidative inactivation of PTEN in the soleus muscle and heart, and TXNIP is phosphorylated by AKT in response to insulin (Hui et al, 2008; Waldhart et al, 2017). To elucidate the correlation between TXNIP and AKT, we examined whether TXNIP interacts with AKT in cells.…”
Section: Resultsmentioning
confidence: 99%
“…Other groups have previously shown that TXNIP deficiency induces AKT activation via oxidative inactivation of PTEN in the soleus muscle and heart, and TXNIP is phosphorylated by AKT in response to insulin (Hui et al, 2008; Waldhart et al, 2017). To elucidate the correlation between TXNIP and AKT, we examined whether TXNIP interacts with AKT in cells.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, USP6NL is mainly localized to the PM (19), a location where the PI3K/AKT signaling axis is generally considered to initiate (39). Finally, AKT phosphorylates the GLUT1 endocytic adaptor TXNIP at the PM, inhibiting the endocytosis of glucose transporters (40). Thus, the concerted action of USP6NL and AKT, acting at the cell surface, might link EGFR signaling to glucose uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, recent research has revealed that TXNIP plays a crucial role in redox-independent signaling [21]. TXNIP was found to inhibit glucose uptake independent of thioredoxin binding, which was important for the survival of thyroid cancer cells [34]. Interestingly, several studies have also shown that the overexpression of TXNIP inhibited HIF-mediated reporter activity in various cancer cells [20,33,35].…”
Section: Discussionmentioning
confidence: 99%